2019
DOI: 10.1111/1750-3841.14774
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Free Chlorine Consumption and Escherichia coli O157:H7 Cross‐Contamination During Fresh‐Cut Produce Wash Cycles

Abstract: Controlling the free chlorine (FC) availability in wash water during sanitization of fresh produce enhances our ability to reduce microbial levels and prevent cross‐contamination. However, maintaining an ideal concentration of FC that could prevent the risk of contamination within the wash system is still a technical challenge in the industry, indicating the need to better understand wash water chemistry dynamics. Using bench‐scale experiments and modeling approaches, we developed a comprehensive mathematical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The advantage of this model is that measuring each of these organic reactants involves complicated analytic methods while measuring COD is relatively quick and straightforward. Moreover, we and other researchers have reported the strong correlation between produce-water ratio and COD levels for various types of produce (Abnavi, Alradaan, Munther, Kothapalli, & Srinivasan, 2019;Li et al, 2019). Therefore, with careful calibration of commercial systems, it is possible that the measurement of COD is redundant.…”
Section: Establishing Chlorine Decay Model Using Single-wash Experimentsmentioning
confidence: 87%
“…The advantage of this model is that measuring each of these organic reactants involves complicated analytic methods while measuring COD is relatively quick and straightforward. Moreover, we and other researchers have reported the strong correlation between produce-water ratio and COD levels for various types of produce (Abnavi, Alradaan, Munther, Kothapalli, & Srinivasan, 2019;Li et al, 2019). Therefore, with careful calibration of commercial systems, it is possible that the measurement of COD is redundant.…”
Section: Establishing Chlorine Decay Model Using Single-wash Experimentsmentioning
confidence: 87%
“…This is similar to our log reductions for S. Newport MDD14 and S. Typhimurium FSL R6-0020. Problems with chlorine washes for produce include the consumption of free chlorine that is necessary to reduce bacterial numbers by fresh-cut produce exudates [ 27 ] and the production of stronger biofilm by the bacteria upon chlorine stress via induction of the oxidative stress response [ 28 ]. In tomatoes, it has been shown that field debris and defective tomatoes at less than 1% make up for 55.5% of the chlorine demand in the wash [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…On leafy greens, chlorine as well as range of other chemicals are used in the wash water to reduce cross-contamination [15]. Intriguingly, the efficacy of such treatments can be limited because of the inactivation of the free chlorine by fresh cut plant exudates, which facilitates cross-contamination during the wash cycles [16]. In addition, bacteria can form biofilms on many surfaces, including stainless steel, when treated with sub-lethal concentrations of the anti-microbial [17].…”
Section: Current Solutionsmentioning
confidence: 99%